Influence of radiographic phenotype on risk of hip osteoarthritis within families. Issue 3 (12th February 2004) - Lanyon, P; Muir, K; Doherty, S; Doherty, M
Abstract : Objective: To determine whether the magnitude of the genetic influence on the development of hip osteoarthritis (OA) varies according to the radiographic phenotype within families. Participants and methods: 331 families in which at least one sibling (index participant) had undergone total hip replacement for OA and whose preoperative x ray findings were available; 505 siblings of these index participants, who have high exposure to genetic risk of hip OA; and 1718 participants who had previously undergone intravenous urography, representative of the average general population exposure to genetic risk. Prevalence of hip OA was determined by individual radiographic features and minimum hip joint space. OA phenotype was partitioned according to pattern of femoral head migration and osteophyte bone response. Age adjusted odds ratios for hip OA in siblings, stratified according to phenotypic pattern in their index sibling, were assessed by unconditional logistic regression. Results: The superior pattern of femoral head migration was more common in men, and the axial pattern more common in women. A poor bone response (absent osteophytosis) was associated with an indeterminate pattern of migration. The age adjusted odds ratios for definite hip OA were twofold higher in siblings of index participants who had no osteophyte response than in siblings whose index case had any degree of osteophyte (OR 2.05, 95% CI 1.12 to 3.76). The risk of the siblings from these families having undergone hip replacement themselves was threefold higher. Patterns of migration and bone response were not concordant within families, even among same sex siblings. Conclusion: Careful phenotypic characterisation is essential for genetic studies of hip OA. The results of these studies are likely to be influenced by the phenotypic pattern of hip disease, particularly osteophyte bone response.